The Effect of Fraction and Active Compounds of Momordica Balsamina L. on Bacteria Salmonella Typhi Causing Salmonellosis - Aryanti Aryanti; Rinda Lamdayani (Indonesian Journal of Global Health Research, 2021)
Salmonella typhi is one of the bacteria that causes typhus. The handling of typhus by bacteria generally requires the provision of antibacterial substances, namely antibiotics. Excessive and irrational use of antibiotics causes bacteria to be resistant so that over time the benefits of using antibiotics will decrease. Pare leaves are an alternative treatment for various diseases, one of which is antibacterial. The purpose of this study was to determine the ability of bitter melon leaf fractions and active compounds against Salmonella typhi bacteria with various concentrations. This study was a laboratory experimental study through in vitro. The subjects in this research were Salmonella typhi bacteria. The results of this study indicated that the concentration of ethyl acetate fraction is a strong fraction between n-hexane and water methanol fractions in inhibiting Salmonella typhi bacteria. The determination of the active compound group from the purification of the ethyl acetate fraction of forest bitter melon leaves obtained flavonoid active compounds with an Rf value of 0.1 in the eluent n-hexane: ethyl acetate (7:3). The minimum inhibitory concentration (MIC) of ethyl acetate fraction was 125 μg/ml, while the MIC of flavonoid compounds was 62.5 μg/ml against Salmonella typhi bacteria. From the results of the equivalence test of the ethyl acetate fraction with ampicillin against Salmonella typhi bacteria, it showed that the concentration of the active fraction of ethyl acetate 1 μg/ml was equivalent to 0.007 μg/ml ampicillin, while the equivalence of flavonoid compounds was obtained 1 μg/ml concentration of active compounds equivalent to 0.011 μg/ml ampicillin.